SINGLE-PHOTON EMISSION COMPUTED TOMOGRAPHY IN COMBINATION WITH X-RAY COMPUTED TOMOGRAPHY IN THE STUDY OF LACRIMAL PASSAGES. FIRST RESULTS - E. L. At’kova; I. O. Tomashevskiy; A. I. Luchshev; V. D. Yartsev (Вестник рентгенологии и радиологии, 2016)
Objective: to explore the capabilities of single-photon emission computed tomography (SPECT) in combination with x-ray computed tomography (SPECT/CT) in the study of the anatomy and drainage function of lacrimal passages.Material and methods. Twelve scans were carried out in 6 healthy volunteers and in patients with different lacrimal drainage disorders (dacryostenoses, varying obstructive lacrimal passage, dacryocystitis and post-dacryocystorhinostomy). Sodium pertechnetate (99mTc) solution and a radiocontrast agent were instilled into the conjunctival sac during the study.Results. SPECT is an objective procedure to study lacrimal drainage function. It cannot provide data on the anatomic structure of lacrimal passages and determine the location of their stenosis or obstruction. SPECT/CT makes it possible to simultaneously obtain information on the anatomic structure of lacrimal passages, to visualize the sites of their pathological changes, and to evaluate the drainage function of lacrimal passages.